Meta-analysis of single-port versus conventional laparoscopic cholecystectomy comparing body image and cosmesis. Issue 9 (1st June 2017) - Haueter, R; Schütz, T; Raptis, D A; Clavien, P-A; Zuber, M
Abstract: Background: The purpose of this study was to evaluate improvements in cosmetic results and postoperative morbidity for single-incision laparoscopic cholecystectomy (SILC) in comparison with multiport laparoscopic cholecystectomy (MLC). Methods: A literature search was undertaken for RCTs comparing SILC with MLC in adult patients with benign gallbladder disease. Primary outcomes were body image and cosmesis scores at different time points. Secondary outcomes included intraoperative and postoperative complications, postoperative pain and frequency of port-site hernia. Results: Thirty-seven RCTs were included, with a total of 3051 patients. The body image score favoured SILC at all time points (short term: mean difference (MD) –2·09, P < 0·001; mid term: MD −1·33, P < 0·001), as did the cosmesis score (short term: MD 3·20, P < 0·001; mid term: MD 4·03, P < 0·001; long-term: MD 4·87, P = 0·05) and the wound satisfaction score (short term: MD 1·19, P = 0·03; mid term: MD 1·38, P < 0·001; long-term: MD 1·19, P = 0·02). Duration of operation was longer for SILC (MD 13·56 min; P < 0·001) and SILC required more additional ports (odds ratio (OR) 6·78; P < 0·001). Postoperative pain assessed by a visual analogue scale (VAS) was lower for SILC at 12 h after operation (MD in VAS score −0·80; P = 0·007). The incisional hernia rate was higher after SILC (OR 2·50, P = 0·03). All other outcomes were similar for both groups. Conclusion: SILC is associated with better outcomes in terms of cosmesis, body image and postoperative pain. The risk of incisional hernia is four times higher after SILC than after MLC. Abstract : Single port superior for cosmesis, body image and pain